Instrumen Perilaku Konsumen sebagai Input Komunikasi Organisasi Eksternal - Damanik, Elsye Rumondang (Bina Nusantara University, 2011)
Towards information technology era, every organization is urged to be able to produce information related to its environment in order to survive and to compete. Information gathering process stage will cause to new concept as a basic for organization in its event planning. The purpose of the article is to acknowledge information function related to consumer behavior as organization communication with the public, analyse, produce, and use it for the interest of organization’s working planning. Every data and information in the article come from literature study by processing information from books and mass media. The result of the article that every organization which aims to increase its quality and quantity performance and to compete continuously must understand the consumer behavior through message exchanging with the public which could be used through personal communication strategy.